Long‐Term Detection of Human Adipose‐Derived Mesenchymal Stem Cells After Intraarticular Injection in SCID Mice. Issue 7 (2nd July 2013) - Toupet, Karine; Maumus, Marie; Peyrafitte, Julie‐Anne; Bourin, Philippe; van Lent, Peter L. E. M.; Ferreira, Rosanna; Orsetti, Béatrice; Pirot, Nelly; Casteilla, Louis; Jorgensen, Christian; Noël, Danièle
Abstract : Objective: Mesenchymal stem cells (MSCs) represent a promising tool for cell therapy for several disorders, among them the osteoarticular diseases. For such clinical applications, intraarticular (IA) injection of MSCs may be favored for higher levels of safety and targeting of specific joints. Although the safety of intravenous (IV) administration of MSCs has been reported in a number of clinical trials, the safety and biodistribution of MSCs after IA injection have not been tested. Our objective was to assess the toxicity of clinical‐grade human adipose‐derived MSCs (AD‐MSCs), as well as their biodistribution, after IA injection into SCID mice. Methods: SCID mice received IA or IV administration of 10 6 human AD‐MSCs. Several tissues were recovered at different time points and processed for histologic assessment or real‐time polymerase chain reaction (PCR) analysis. A highly sensitive assay was used to monitor the distribution of AD‐MSCs, based on amplification of human‐specific Alu sequences. Results: Absence of toxicity was observed after AD‐MSC infusion. Alu PCR assay revealed a high sensitivity (1 human AD‐MSC/10 5 murine cells), with a large linear range (1–5 × 10 4 /10 5 murine cells). Importantly, 15% of the IA‐injected AD‐MSCs were detectable in the joint for the first month and 1.5% of the AD‐MSCs engrafted over the long term, at least 6 months. AD‐MSCs were observed in the injected joints and in areas of tissue referred to as stem cell niches, such as the bone marrow, adipose tissue, and muscle. Conclusion: These data support the feasibility and safety of using IA delivery of human AD‐MSCs in the treatment of rheumatic diseases that affect the joints.